Pengaruh Motivasi Belajar Terhadap Minat Pembelajaran Penjas Siswa SMPN 18 Kota Cirebon - Achmad Zakaria; Adiman Adiman; Syifa Nurbait (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine the effect of learning motivation on interest in physical education (PE) among eighth-grade students at SMPN 18 Kota Cirebon. Learning motivation is an important factor that encourages students to be more active and interested in the learning process, especially in PE, which requires both physical and mental involvement. Materials and method. This study employed a pre-experimental method with a one-group pretest-posttest design. The research subjects were 31 eighth-grade students from Class VIII A. Data collection instruments consisted of a closed-ended questionnaire using a Likert scale to measure motivation and learning interest levels before and after the intervention. The intervention involved instruction using the demonstration method. Data analysis was conducted using linear regression analysis with the assistance of SPSS software. Results. The results showed that learning motivation significantly influenced interest in physical education learning. The increase in motivation through the demonstration method was proven to enhance students' interest in participating in learning. Conclusions. Therefore, physical education teachers are advised to maximise the use of interactive learning methods such as demonstrations to encourage students' motivation and interest in learning.